An exploration of barriers and enablers of retention in a program to reduce vertical transmission of HIV at health centers in Zimbabwe - Augustine Ndaimani; Inam Chitsike; Clara Haruzivishe; Babill Stray-Pedersen (International Journal of Preventive Medicine, 2019)
Background: Poor retention in the prevention of women in prevention of vertical transmission programs remains a formidable common setback in elimination of HIV/AIDS. It creates new problems such as poor health outcomes and increased incidence of vertical transmission of HIV. There is a dearth of qualitative information to explain poor retention of women in prevention of mother-to-child transmission (PMTCT) programs in Zimbabwe. The purpose of the study was to explore the enablers and barriers of retention of women in PMTCT programs. Methods: This was a basic qualitative study conducted at four health centers in Zimbabwe. Four audiotaped focus group discussions were conducted with 34 pregnant or breastfeeding women coming for PMTCT services at the health centers. Descriptive statistics was used for sample demographics. Transcripts were analyzed through latent content analysis based on the Graneheim and Lundman method. Results: Maternal determination, a four-tier support system, and an inspiring health package were enablers to retention in the PMTCT program while uninspired individual engagement, paternalism, and undesirable PMTCT-related events were barriers to retention of women in the PMTCT program. Conclusions: Reinforcing hope for the women and their children, active management of side effects of antiretroviral medicine, consistent peer support, enhancing confidentiality among community cadres, and commitment from community or religious leaders may improve retention of women in PMTCT programs; for women with HIV during pregnancy, delivery and post-natal care.